2002
DOI: 10.1097/00002371-200209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Patients With Disseminated Malignant Melanoma by Vaccination With Autologous Cell Hybrids of Tumor Cells and Dendritic Cells

Abstract: Malignant melanoma has been shown to be susceptible to T cell-mediated immunity and, therefore, is a candidate for vaccination approaches. Clinical trials using dendritic cells (DC) loaded with peptides corresponding to tumor antigens are ongoing in several institutions, and some promising results have already been published. However, every single peptide-based vaccine can only be used in a patient with a given single HLA type, and this strategy is not appropriate for patients with rare HLA types or with tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 32 publications
3
45
0
1
Order By: Relevance
“…In preclinical murine models, DC-TC hybrids have stimulated potent protective and therapeutic immune responses to carcinomas, lymphomas, melanomas, and gliomas (23)(24)(25)(26)(27)(28)(29). However, in two recent human clinical trials, fusions of DCs and autologous tumor cells were primarily ineffective for the treatment of patients with melanoma and glioma (35,36). In both of these protocols, PEG was used as the fusogenic reagent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preclinical murine models, DC-TC hybrids have stimulated potent protective and therapeutic immune responses to carcinomas, lymphomas, melanomas, and gliomas (23)(24)(25)(26)(27)(28)(29). However, in two recent human clinical trials, fusions of DCs and autologous tumor cells were primarily ineffective for the treatment of patients with melanoma and glioma (35,36). In both of these protocols, PEG was used as the fusogenic reagent.…”
Section: Discussionmentioning
confidence: 99%
“…Two human clinical trials have been reported in which patients with melanoma (35) or malignant glioma (36) were vaccinated with autologous DC-TC hybrids made with the fusogenic agent polyethylene glycol (PEG). Although the treatments were safe and well-tolerated, few clinical responses were observed.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…This was measured by post-therapy increment in antitumour cytolytic activity, by increased cytokine production of lymphocytes to tumour antigens and by rearranged TCR repertoire, which indicates the expansion of specific clones, in peripheral blood or within the tumour (Soiffer et al, 1998;Krause et al, 2002;Manne et al, 2002). DTH reaction to tumour cells is a useful clinical test that reflects cell-mediated antitumour immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Various fusion cells have been constructed by alternating the fusion partners, DC, and/or tumor cells. DC have been fused to autologous tumor cells [2][3][4][5]. In this case, the tumor antigens, known or unidentified, can be fully presented in the context of self HLA class I and class II molecules to autologous T cells.…”
Section: Introductionmentioning
confidence: 99%